THE ROLE OF MACRO-MONETARY POLICY ON ISLAMIC BANKING STABILITY IN THE BUSINESS CYCLE IN INDONESIA: STUDY OF KEYNES'S THEORY AND IBN KHALDUN'S THEORY - Yudi Yudi (Jurnal Ilmiah MEA (Manajemen, Ekonomi, & Akuntansi), 2022)
According to the theory of Keynes and Ibn Khaldun, the government must be in control of the national economy with active policies to influence the movement of the economy. The macro-monetary policy can reduce output imbalances through macro-monetary instruments to influence credit growth, affecting aggregate demand. This study aims to analyze the role of macro-monetary policy on Islamic banking stability in the business cycle in Indonesia. This study used the Vector Error Correction Model (VECM) simultaneous equation method with the Eviews-12 program. This study used secondary data on Islamic banks from various institutions such as the Financial Services Authority, Bank Indonesia and the Central Bureau of Statistics. The secondary data in this study are Islamic banks from 2008 to 2021. This research resulted in findings that, in the long-term business cycle, Statutory Reserves positively influence Islamic banking financing. Buffer capital or Capital Buffer and Non-Performing Financing negatively influence sharia banking financing. Meanwhile, economic growth or Gross Domestic Product does not affect sharia banking financing. Meanwhile, in the short term, none affects sharia banking financing. The results of the Impulse Response Function (IRF) and Forecast Error Variance Decompositions (FEVD) show that the shock of the Statutory Reserves and Buffer Capital makes the most significant contribution to sharia banking financing in the long-term business cycle. The results of this study can encourage Islamic banks to use macro-monetary instruments in controlling Islamic financing as a proxy for the stability of Islamic banking in Indonesia to control the distribution of financing in a balanced, prudent and quality manner in the business cycle. Then it can anticipate losses and not disrupt the stability of Islamic Banks.